Intercâmbio universitário Brasil-China : trajetórias formadoras de estudantes do Rio Grande do Sul participantes do Programa Ciência sem Fronteiras - Liu, Luoyuan (2018)
This dissertation sought to analyze the global citizenship development process of students from Rio Grande do Sul who participated in the Science without Borders Program and chose China as destination for the exchange experience. Data analyzed for the study was collected via the distribution of a questionnaire to former Program participants, which elicited twenty responses, and through in-depth interviews conducted with four undergraduate students from Rio Grande do Sul. This study, in particular, sought to draw a correlation between academic mobility and the development of global citizenship. The experiences of the students were diverse: with participants detailing both insights gained about China and its people as a result of the Program, as well as a variety of personal developments. Whilst students identified some flaws with the Science without Borders Program, they emphasized a number of key practical benefits, including an improved proficiency in their chosen language and an enhanced understanding of their recipient country. Students also more generally noted a deepened understanding of and respect for cultural diversity and cultural differences, a broadened world view, and an elevated sense of independence and self-confidence. Above all, research revealed a strong correlation between the experience of academic mobility and the students’ development of global citizenship.